The euro changeover and price adjustments in Italy - Guglielmo Maria Caporale; Alessandro Girardi; Marco Ventura (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
By estimating a staggered price model over the period 1980q1-2010q2, this paper documents that, after the euro changeover, Italian retailers have increased the number of price adjustments, which has translated into a higher inflation rate, with a detrimental effect on the competitiveness of the Italian economy.
Keywords: C22; E31; 330; euro changeover; staggered price adjustments; inflation; Euro; Währungsumstellung; Einzelhandelspreispolitik; Anpassung; Inflation; Italien